Trading secrets : spies and intelligence in an age of terror - Huband, Mark (London: I.B. Tauris, 2013)
Drawing on previously unseen material, unpublished letters and exclusive interviews, this title explores how the role and purpose of 'intelligence' has evolved from its origins in nineteenth-century Ireland to today's fight against terrorism.
1. "The craft of cheat and imposter" -- 2. The first intelligence war -- 3. Talking to terrorists -- 4. Making spies -- 5. Games without frontiers -- 6. The Osama method -- 7. The road to 9/11 -- 8. Guantanamo days -- 9. Prisoners -- 10. Know your enemy -- 11. "Hail the Chief" -- 12. Shadow wars -- Epilogue.
Includes bibliographical references (pages 229-249) and index.
Keywords: Espionage -- History; Spies -- History